Florida Crop/Pest Management Profiles: Citrus (Oranges/Grapefruit) - Mark A. Mossler (EDIS)
Did you know that Florida growers produced 79 percent of the oranges harvested in the United States in 2008-2009? Learn about citrus production in Florida — production facts, production regions, production practices, worker activities, and major pests. This revised 18-page fact sheet was written by M.A. Mossler and published by the UF Department of Horticultural Sciences, January 2011.